Unified Train Driving Policy - Iliasov, Alexei; Lopatkin, Ilya; Romanovsky, Alexander (Formal Methods Applied to Complex Systems: Implementation of the B Method, 2014)
This chapter presents a domain‐specific formal modeling language uniformly addressing fixed and moving block principles in both discrete and continuous contexts. An objective of this work is to help signaling engineers to reason about safety and performance within the scope of a single railway model and thus help them to design safe railway networks that achieve higher capacity. The chapter proposes a modeling notation called Unified Train Driving Policy (UTDP). It introduces the UTDP modeling notation based on the constraint concept and shows how to use it to indirectly define horizon, evolution and mutation of actors, in particular actors modeling train progress through a railway network. The chapter demonstrates invariants and hazards, we must also prove that a given UTDP specification satisfies the well‐formedness condition and behavioral constraints are satisfiable.